2009
DOI: 10.1189/jlb.0609388
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2A receptor activation limits graft-versus-host disease after allogenic hematopoietic stem cell transplantation

Abstract: GVHD is a major barrier to broader use of allogenic HSCT for nonmalignancy clinical applications such as the treatment of primary immunodeficiencies and hemoglobinopathies. We show in a murine model of C57BL/6J (H2-k(b)) --> B6D2F1/J (H2-k(b/d)) acute GVHD that when initiated 2 days before transplant, the activation of the adenosine A(2A)R with the selective agonist ATL146e inhibits the weight loss and mortality associated with disease progression. Furthermore, circulating levels of proinflammatory cytokines a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 43 publications
8
46
0
Order By: Relevance
“…Furthermore, CD73-generated adenosine is known to inhibit proinflammatory cytokine production, 28 to decrease the expression of adhesion molecules on endothelial cells, 49 and to inhibit endothelial permeability, 7 actions that should reduce the severity of GVHD. Our findings extend the observations of Lappas et al 13 who showed that pharmacologic activation of the A 2A AR can reduce the severity of GVHD. In contrast, our results showed that endogenous levels of A 2A AR signaling reduced the expansion of allogeneic T cells and demonstrated that CD73 was the source of a significant portion of the activating ligand.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, CD73-generated adenosine is known to inhibit proinflammatory cytokine production, 28 to decrease the expression of adhesion molecules on endothelial cells, 49 and to inhibit endothelial permeability, 7 actions that should reduce the severity of GVHD. Our findings extend the observations of Lappas et al 13 who showed that pharmacologic activation of the A 2A AR can reduce the severity of GVHD. In contrast, our results showed that endogenous levels of A 2A AR signaling reduced the expansion of allogeneic T cells and demonstrated that CD73 was the source of a significant portion of the activating ligand.…”
Section: Discussionsupporting
confidence: 92%
“…14 Another A 2A AR agonist was shown to attenuate acute GVHD after allo-HCT. 13 These findings support the concept that extracellular adenosine counteracts ATPtriggered immune activation as a negative feedback mechanism to prevent uncontrolled tissue destruction because of excessive inflammation.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…29,83,84 The protective role of adenosine signaling via the Adora2a in GVHD is also supported by studies demonstrating that treatment of animals with the selective Adora2a agonist ATL146e reduces cardinal features of GVHD by enhancing the number of donor-derived Tregs. 85,86 In summary, these studies indicate that ATP signaling through the P2X 7 R is associated with enhanced generation of allogeneic donor T cells and suppression of Tregs, thereby contributing to the development of GVHD. In contrast, CD73-dependent adenosine generation and signaling through the Adora2a dampens GVHD via inhibition of allogeneic T cells and promotion of donor Tregs.…”
Section: Graft-versus-host Diseasementioning
confidence: 80%
“…Activated Tcons proliferate and trigger release of alarmins, such as IL-33 and its soluble receptor ST2, from non-HP APCs, such as stromal cells and endothelium; these activated Tcons also express the integrin receptor α 4 β 7 , which directs their migration back to intestinal tissue after entering the villus capillaries. the absence of CD73 on either donor T cells or host APCs exacerbated GVHD (54)(55)(56). UA, a purine metabolite released from damaged cells, is an endogenous DAMP that stimulates DCs and activates CD8 + T cell cytotoxic functions (45,57).…”
Section: Immune Homeostasis In the Gi Tractmentioning
confidence: 99%